Computer-Assisted Language Learning: The Impact in Language Education - Nur Ima; Adriani Jihad (Yayasan Vifada Cendikia Indonesia, 2024)
Computer-Assisted Language Learning (CALL) has become an increasingly integral component of language education, offering a diverse array of tools and resources to enhance the teaching and learning of languages. This article explores the integration of CALL in language education, examining its impact on pedagogy, and the overall or learning experience.Additionally, based on this research Computer-Assisted Language Learning (CALL) has significantly impacted language education, offering transformative opportunities for language learners and educators alike. By harnessing the power of technology, CALL has the potential to revolutionize language education, fostering inclusive, interactive, and personalized learning experiences in the digital era.